2003
DOI: 10.1097/00002060-200301000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Hemorrhagic Transformation in Stroke Patients

Abstract: Hemorrhagic transformation of an ischemic lesion does not affect rehabilitation outcome in stroke survivors. The study results favor the use of anticoagulants and antiaggregants in the acute phase unless these drugs are contraindicated by the patient's condition. Still, prospective trials are needed to make definite conclusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…A recent study found that hemorrhagic transformation in stroke patients was detected in one third of patients admitted to acute rehabilitation, but functional outcome was not significantly different from that of patients who did not have hemorrhagic transformation on the first CT scan. 728 Hemorrhagic conversion in patients with cerebellar infarct significantly increased the risk of deterioration. 729 Recently, it has been suggested that gadolinium enhancement on T1-weighted MR images is predictive of hemorrhagic transformation, but this finding is unconfirmed.…”
Section: B Hemorrhagic Transformationmentioning
confidence: 99%
“…A recent study found that hemorrhagic transformation in stroke patients was detected in one third of patients admitted to acute rehabilitation, but functional outcome was not significantly different from that of patients who did not have hemorrhagic transformation on the first CT scan. 728 Hemorrhagic conversion in patients with cerebellar infarct significantly increased the risk of deterioration. 729 Recently, it has been suggested that gadolinium enhancement on T1-weighted MR images is predictive of hemorrhagic transformation, but this finding is unconfirmed.…”
Section: B Hemorrhagic Transformationmentioning
confidence: 99%
“…Evacuation of a large hemorrhage may be lifesaving, whereas smaller hematomas may be tolerated without clinical relevance. 999 As with cerebral edema, cerebellar hemorrhagic conversion is more likely to become symptomatic.…”
Section: Hemorrhagic Transformationmentioning
confidence: 99%
“…Many believe that so-called hemorrhagic transformations are part of the natural history of acute ischemic stroke and are clinically innocuous, a "CT scan event" without any adverse sequela. 3,4 Indeed, several studies have been unable to detect any effect on overall prognosis once other factors associated with a poor prognosis are accounted for. 4 -6 However, previous studies have had several important limitations, including relatively small samples and the absence of any power calculations.…”
mentioning
confidence: 99%